Haematological and Biochemical Characterization of Bubaline Trypanosomosis in Mumbai Region of India - Gudewar, J. G.; Birajdar, P. G.; Palampalle, H. Y.; Gatne, M. L.; Dalvi, S. H. (Journal of Buffalo Science, 2014)
The present study was based on observations on 17 cases of Trypanosoma evansi infection in buffaloes diagnosed by blood smear examination. The degree of parasitaemia revealed heavy (64.70%), moderate (23.52%) and mild (11.76%) infections in buffaloes.Haematological analysis revealed subnormal erythrocytic count and haemoglobin in 70.58% buffaloes. Leukocytosis was evident in 70.58% buffaloes with neutrophilia relatively associated with lymphocytopenia.Blood glucose level of 15 hypoglycaemic buffaloes ranged between 27 to 49.05 gm/dl with an average of 39.35 gm/dl. The comparative analysis of the degree of hypoglycaemia with parasitaemia revealed positive correlation between two parameters. Biochemical analysis of sera and blood samples showed increase level of BUN and serum creatinine in 17.64% buffaloes.